(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Carbon structural steels do not fully meet the requirements of high accuracy even after heat treatment, small depth of penetration, embrittlement at low temperature, low corrosion tolerance, as well as high thermal expansion coefficient of carbon tool steels, high temperature aggressive environments due to the development of certain new fields such as rocket, jet and nuclear technology, due to the development of certain new fields such as high temperature range, high pressure and aggressive environments, the need for materials increased [1,2].